Precise Temperature Stabilizing System of Liquids for the purpose Biomedical Applications - Vozda, M.; Sekora, J.; Penhaker, M. (Elektronika ir Elektrotechnika, 2012)
This paper describes the design of equipment for measuring and temperature control solutions with an accuracy of temperature measurement to ± 0.2 °C from 25 °C to 45 °C. It describes the basic blocks of the proposed facility and the results obtained in testing the liquid volume to 2 litre. The proposed facility is designed as an autonomous system, but allows setting and displaying the control on your compute. The device implements two algorithms and autonomic control of the PSD and the tri-state control. Designed and implemented system for temperature control solutions is fully operational and immediately applicable to real requirements in practice. DOI: http://dx.doi.org/10.5755/j01.eee.18.10.3056